2022
DOI: 10.3390/pharmaceutics14061224
|View full text |Cite
|
Sign up to set email alerts
|

Relation between Plasma Trough Concentration of Pazopanib and Progression-Free Survival in Metastatic Soft Tissue Sarcoma Patients

Abstract: Background: Pazopanib (PAZ) is an oral angiogenesis inhibitor approved to treat soft tissue sarcoma (STS) but associated with a large interpatient pharmacokinetic (PK) variability and narrow therapeutic index. We aimed to define the specific threshold of PAZ trough concentration (Cmin) associated with better progression-free survival (PFS) in STS patients. Methods: In this observational study, PAZ Cmin was monitored over the treatment course. For the primary endpoint, the 3-month PFS in STS was analyzed with l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…41 Noda et al 8 also suggested a therapeutic concentration range of 20.5–50.3 mcg/mL in patients with RCC. Recently, Minot-This et al 47 confirmed a target C trough > 27 mcg/mL in a large cohort of patients with STS ( N = 95). This recommendation was based on the finding that a longer OS was observed in patients with C trough > 27 mcg/mL on day 15 compared with patients with C trough between 12.0 and 27 mcg/mL.…”
Section: Resultsmentioning
confidence: 89%
See 4 more Smart Citations
“…41 Noda et al 8 also suggested a therapeutic concentration range of 20.5–50.3 mcg/mL in patients with RCC. Recently, Minot-This et al 47 confirmed a target C trough > 27 mcg/mL in a large cohort of patients with STS ( N = 95). This recommendation was based on the finding that a longer OS was observed in patients with C trough > 27 mcg/mL on day 15 compared with patients with C trough between 12.0 and 27 mcg/mL.…”
Section: Resultsmentioning
confidence: 89%
“…41 Noda et al 8 also suggested a therapeutic concentration range of 20.5-50.3 mcg/mL in patients with RCC. Recently, Minot-This et al 47 confirmed a target C trough . 27 mcg/mL in a large cohort of patients with STS (N = 95).…”
Section: Exposure-response Relationshipmentioning
confidence: 93%
See 3 more Smart Citations